Cost effective DIY Smartphone based Retinal Imaging - Gupta, Shubhi; Kumar, Akhilesh; Thakur, Sanjeev; Gupta, Ashutosh; Vashisht, Swati; Singh, Divya (2021 2nd International Conference on Intelligent Engineering and Management (ICIEM), 2021)
Images of retina of high quality with a wide field is a powerful form of classifying and detecting retinal diseases. These are preventable however can jeopardize vision. Retinal cameras dependent on cell phones hold guarantee to expand admittance to retinal symbolism, however various characteristics of picture and protected area of view will diminish their value. Our paper proposes fundus camera dependent on your own cell phone that can take photographs of the focal retina as well as the fringe retina at a plana standards. This may be demonstrated well as a methodology less expensive to the camera zeroing in on fundus pictures.